Core/shell structured C/ZnO nanoparticles composites for effective electromagnetic wave absorption. Issue 8 (15th January 2016) - Han, Meikang; Yin, Xiaowei; Ren, Sa; Duan, Wenyan; Zhang, Litong; Cheng, Laifei
Abstract : Core/shell structured C/ZnO nanoparticles composite exhibits an effective strategy to design high-performance microwave absorbing materials with adjustable impedance match. Abstract : Core/shell structured C/ZnO nanoparticles were synthesized by a two-step process based on hydrothermal method. The experimental results show that ZnO nanoparticles attach on the surface of carbon spheres through the surfacial functional groups. The core/shell structure enhances the electromagnetic wave attenuation capability owing to defects, multiple interfaces and optimal impedance match. Different mass percentages of C/ZnO nanoparticles were mixed in paraffin wax to investigate the electromagnetic wave absorbing and shielding performance. When the filler loading is 40 wt%, the composite shows a minimum reflection coefficient of −52 dB at 11 GHz with a sample thickness of 1.75 mm. When the mass ratio is 50 wt%, the sample has an electromagnetic shielding performance of 14.85 dB dominated by absorption. Compared with pure carbon spheres and ZnO hollow spheres, the core/shell structure of C/ZnO composites exhibits a promising route to design electromagnetic wave absorbing materials with high dielectric loss and moderate impedance match.